(untitled) (Universitas Medica, 2021)
Since the end of the 20th century, the lactate levels have been studied as a prognostic marker in critically ill patients and as a goal in their resuscitation. In patients with liver disease, the interpretation of lactate levels presents some difficulty given its pathophysiological production mechanism. However, there is evidence on the relationship between lactate levels and mortality in patients with acute or chronic liver disease in critically ill patients. In addition, lactate has been postulated as a predictor of benefit from liver transplantation and an early prognostic marker after liver transplantation. Thus, the study and adequate interpretation of lactate in patients with liver disease is relevant.